Fundamentals of renewable energy processes - Da Rosa, Aldo Vieira (Elsevier Academic Press, 2013)
With energy sustainability and security at the forefront of public discourse worldwide, there is a pressing need to foster an understanding of clean, safe alternative energy sources such as solar and wind power. Aldo da Rosa's highly respected and comprehensive resource fulfills this need; it has provided thousands of engineers, scientists, students and professionals alike with a thorough grounding in the scientific principles underlying the complex world of renewable energy technologies. This new third edition of the classic text highlights advances in this vital area, which are proceeding at an unprecedented pace, allowing everyone interested in this burgeoning field to keep up with the latest developments in diverse topics from solar cooling to renewable energy storage.